Implementasi Steganografi Least Significant Bit (LSB) untuk Penyembunyian File dalam Gambar Digital Berbasis CustomTkinter - Muhammad Angga Fernanda; M. Lathifurrahman; Adhitya Wahyu Ardhana; Dedi Sukhairi Gea (JIKUM: Jurnal Ilmu Komputer, 2026)
Information security has become increasingly critical in the digital era, particularly concerning confidential data protection. Steganography is a method used to hide information within digital media without arousing suspicion. This research implements the Least Significant Bit (LSB) steganography technique for embedding secret files within digital images using Python with CustomTkinter framework. The system provides an intuitive graphical user interface for encryption and decryption processes with real-time capacity validation. The LSB method works by replacing the least significant bits of image pixels with secret file bits, maintaining visual quality while securing hidden data. Testing demonstrates that the system successfully embeds and extracts various file types with capacity validation to prevent overflow errors. The system supports multiple file formats with output saved in PNG format to preserve data integrity. This implementation provides a practical solution for secure data transmission through digital images with user-friendly interface suitable for various users.